2011
DOI: 10.4049/jimmunol.1101243
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Skews Dendritic Cell Differentiation to an Unconventional Phenotype with Tolerogenic Features

Abstract: Dendritic cells (DCs) are critical regulators of immune responses that integrate signals from the innate and adaptive immune system and orchestrate T cell responses toward either immunity or tolerance. Growing evidence points to the Wnt signaling pathway as a pivotal piece in the immune balance and focuses on DCs as a direct target for their immunoregulatory role. Our results show that the increase in Wnt5a signaling during the differentiation of human DCs from monocytes alters their phenotype and compromises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 50 publications
10
69
0
Order By: Relevance
“…Of note, no significant reduction of Wnt-induced cytokine mRNA expression and production was observed in macrophages deficient for TLR2 and the TLR coreceptor, RP105 [30] (data not shown). Similar to previous reports, we observed diminished inflammatory cytokine production upon TLR2 stimulation with Pam 3 CSK 4 [24,26] and TLR9 stimulation with CpG oligonucleotides in macrophages that had been preexposed to recombinant Wnt5a and Wnt3a (Fig. 5A and B).…”
Section: The Effects Of Wnt5a and Wnt3a On Macrophage Inflammatory Resupporting
confidence: 79%
See 1 more Smart Citation
“…Of note, no significant reduction of Wnt-induced cytokine mRNA expression and production was observed in macrophages deficient for TLR2 and the TLR coreceptor, RP105 [30] (data not shown). Similar to previous reports, we observed diminished inflammatory cytokine production upon TLR2 stimulation with Pam 3 CSK 4 [24,26] and TLR9 stimulation with CpG oligonucleotides in macrophages that had been preexposed to recombinant Wnt5a and Wnt3a (Fig. 5A and B).…”
Section: The Effects Of Wnt5a and Wnt3a On Macrophage Inflammatory Resupporting
confidence: 79%
“…Recent studies showed that monocytes, macrophages, DCs, and microglia when preexposed to recombinant Wnt3a and Wnt5a displayed phenotypic changes upon subsequent TLR stimulation, including impaired proinflammatory cytokine expression, elevated IL-10 production, and NF-κB p50-homodimers [21,[24][25][26]. Molecular mechanisms underlying the deactivation by recombinant Wnt3a and Wnt5a remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt 5a had no effect on LPS-induced DC maturation but impaired the production IL-12p70 and TNF- α while increasing levels of IL-10. Furthermore, Wnt 5a inhibited the T cell proliferation and fail to prime T cell response [95]. So the two types of signal pathway display an opposite effect and sustain the regulation of DCs differentiation by crosstalking to each other.…”
Section: The Potential Mechanisms Involving Changes Of DC During Smentioning
confidence: 99%
“…Exposure to Wnt5a resulted in increased secretion of IL-10 in blood-derived monocytes. 40 DCs exposed to this ligand express more indolamin-2, 3-dioxygenase, a tryptophan-degrading enzyme with immune regulatory properties, and induce more regulatory T cells. 41 Taken together, these data strongly suggest that Wnt/β-catenin as well as noncanonical Wnt ligands have the ability to shape DCs to a tolerogenic status and thus preventing or regulating adaptive T-cell responses.…”
Section: Dendritic Cellsmentioning
confidence: 99%